Nutrient Dynamics in Soil Solution and Wheat Response after Biomass Ash Amendments. (1st November 2016) - Mercl, Filip; Tejnecký, Václav; Száková, Jiřina; Tlustoš, Pavel
Abstract : Among the possible methods for biomass ash (BA) utilization, land application represents an important nutrient‐saving approach of BA management. The land application of BA results in an increase of soil pH, but in contrast to conventional liming, ash application on agricultural land can supply additional nutrients to soil, such as K, Mg, or P. However, due to the complex mineral phase composition of ashes, release of nutrients from the ash matrix into soil solution is not well understood. In the presented pot experiment, two agricultural soils were amended using two common types of BA (wood and straw ash) at rate 1% (w/w). During the vegetation period of spring wheat ( Triticum aestivum L.), soil solution was sampled and monitored for the concentrations of Ca, K, Mg, and P. Subsequently, yield and nutrient uptake of wheat were determined. The effect of ash application on the investigated parameters differed substantially between the tested soils. Positive yield responses were found in soil with higher N content. Straw ash application increased concentrations of all monitored nutrients in soil solution but simultaneously increased plant uptake of K and P only. Wood ash increased concentrations of Ca and Mg in solution, while its effect on nutrient uptake strongly differed between soils. Generally, higher relative increases of nutrients in soil solution were surprisingly found in soil with higher pH and higher cation exchange capacity (CEC). Factors influencing dynamics of ash‐contained nutrients in soil solution are discussed. Nutrient leaching from straw and wood ash matrix in soil‐plant conditions is investigated. The influence of ashes on yield and nutrient uptake differed substantially depending on types of ash and soil. Highly soluble K‐compounds in straw ash revealed by X‐ray powder diffraction. Straw ash is a much more efficient P source than wood ash.